Preparation and Acceptability of Guava Cheese - Singh, Harjinder; Kachwaya, Dilip Singh; Vikas, Ghumare (Journal of Postharvest Technology, 2016)
Guava cheese is the chewable confectionary item containing sugar and butter as the  major ingredients. Seeds are removed and make fine pulp. According to recipe or  treatment combinations the mixture heated up to 700Brix.Then citric acid and salt  solution was added and heated up to 770Brix. Then allowed to cool and set. The  organoleptic evaluation was carried out of prepared guava cheese. Present  experiment was laid out in Completely Randomized Design (CRD) with five  treatments viz. T1- Guava pulp (1kg) + Sugar (1 kg) + Ghee (100g), T2 - Guava  pulp (1kg) + Sugar (1.2 kg) + Ghee ( 100 g), T3 - Guava pulp (1kg) + Jaggery (1kg)  + Ghee (100 g), T4 - Guava pulp (1kg) + Jaggery (1.2 kg) + Ghee (100g), T5 - Guava pulp (1kg) +Artificial sweetener + Ghee (100 g) were used for formation of  guava cheese. Each treatment was replicated four times. The results of the research  shows that the guava cheese formed from use of Jaggery 1.2 kg along with 1kg  guava pulp and 100g ghee shows good organoleptic rating (7.20) and better quality  parameters. However the present investigation of use of different treatment  combinations shows a non significant interaction between different treatment  combinations. Thus treatment combination in which Jaggery 1.2 kg along with 1 kg  guava pulp and 100g ghee was considered the most benefit tested one for formation  and acceptability of guava cheese having good texture, colour and taste. This is less  costly and farmers could easily adopt to increase their income by formation of  guava cheese in the glut period.
Keywords: Artificial sweetener; Guava cheese; Jaggery; Organoleptic; evaluation Sugar